Kasunanan dan Mangkunegaran di Tengah Pendudukan Jepang - Kris Hapsari (Indonesian Historical Studies, 2018)
This paper discusses the Kasunanan and Mangkunagaran during the Japanese occupation that was compiled using the historical method using primary sources from ANRI and Mangkunegaran. This article is like a prologue from the story of Kasunanan and Mangkunegaran in 1945-1950, the struggle period of the two Surakarta monarchies which maintained their existence in the midst of the independence revolution. The initial story fragment, a brief description of the situation in Surakarta during the Japanese occupation. This short period considered by the Kasunanan and Mangkunegaran became alignments to Japan. This is one of the reasons why was the anti-self-government group wants Surakarta did not become a special region.